Strzała czy oszczep? Problem hamburskich jednozadziorców w świetle badań eksperymentalnych - Łapa, Michał
The first people to re-colonize the European Plain were hunter-gatherer groups identified with the Hamburg culture. These groups actively hunted and for hunting they used weapons tipped with a specific type of points, called the Hamburgian shouldered points (Kerbspitze). To this day, there is an ongoing debate among scientists about setting these blades in motion, which gives rise to two dominant theories. The technology of the bow and arrow is opposed to the technology of the thrower and dart. This paper aims to bring closer the problems of this issue. By juxtaposing the interpretation of hunting-related artefacts, the analysis of Hamburg blades from the Olbrachcice 8 site and an archaeological experiment carried out with the use of replicas of hunting tools, it will try to identify the dominant technology used by Hamburgian reindeer hunters.
Keywords: experimental archaeology; Late Glacial; spear thrower; Hamburgian; shouldered points